Roles and Responsibilities of Notaries in Making Certificates of Inheritance Rights for the Disbursement of Time Deposit Savings Funds by Heirs - Yanita, Novinia (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
This writing aims to find out and analyze the role and responsibilities of Notaries in making certificates of inheritance rights for the disbursement of time deposit savings funds by heirs, the obstacles and ways to overcome obstacles faced by Notaries in making certificates of inheritance rights for disbursement of time deposit savings funds by heirs, and a sample deed of certificate of inheritance rights for the disbursement of time deposit savings funds by the heirs. This research uses empirical legal research. In this research, the object of study is sociological juridical legal research. The analytical knife in this writing uses the theory of legal responsibility and the theory of legal certainty. The results of the research show that the role of a notary in making a certificate of inheritance rights for the disbursement of time deposit savings funds by the heirs is to carry out a certificate of inheritance rights according to procedures. Notary responsibilities include the Notary's civil responsibilities regarding the material truth of the Deed he or she makes, in the construction of an unlawful act. The obstacles faced by notaries include legal substance, legal structure and legal culture. The way to overcome the obstacles that occur is that the Notary as the letter maker is more careful, the Notary needs to know and understand all the provisions that apply to certificates of inheritance rights in Indonesia. Keywords: Certificate; Deposit; Inheritance; Time.